2023
DOI: 10.5114/ceh.2023.131225
|View full text |Cite
|
Sign up to set email alerts
|

Trends of infections and mortality due to hepatitis B virus (2005-2022) and the potential impact of the COVID-19 pandemic: a population-based study in Poland

Agnieszka Genowska,
Dorota Zarębska-Michaluk,
Piotr Tyszko
et al.

Abstract: Aim of the study To analyze the hepatitis B virus (HBV) infection and mortality in Poland according to sociodemographic characteristics, trends over time, and the impact of the COVID-19 pandemic on hepatitis B epidemiology. Material and methods We examined HBV infection cases and deaths reported by national registries and used Joinpoint analysis to estimate time trends in the years 2005-2021. To assess the impact of the COVID-19 pandemic on HBV infection, we used monthl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A decline in new cases was noticed only after 20 years from the start of vaccination [ 40 ]. There are literature reports of a decreased diagnosis rate of HBV infections during the COVID-19 pandemic [ 41 ]. Our study covers only 2 years of that period, 2020 and 2021, with only a small decrease observed during these 2 years when compared to the 2018–2019 period (six vs. eight new cases/year).…”
Section: Discussionmentioning
confidence: 99%
“…A decline in new cases was noticed only after 20 years from the start of vaccination [ 40 ]. There are literature reports of a decreased diagnosis rate of HBV infections during the COVID-19 pandemic [ 41 ]. Our study covers only 2 years of that period, 2020 and 2021, with only a small decrease observed during these 2 years when compared to the 2018–2019 period (six vs. eight new cases/year).…”
Section: Discussionmentioning
confidence: 99%
“…Wilcoxon’s signed-rank test was used to compare the distributions of HAV diagnosis rates between rural and urban settings. In order to explore the long-term trends in new HAV infections during the 2009–2022 period, joinpoint regression was performed to examine changes in the trends [ 23 , 24 ]. We started with the minimum number of joinpoints (e.g., zero joinpoints, which is a straight line) and used a maximum of two joinpoints (corresponding to three-line segments).…”
Section: Methodsmentioning
confidence: 99%